Sternal Resection for Breast Cancer Metastases - Sponholz, Stefan; Baldes, Natalie; Schirren, Moritz; Oguzhan, Selma; Menke, Henrik; Schirren, Joachim (The Thoracic and Cardiovascular Surgeon, 2018)
Background Sternal infiltration of breast cancer (BC) is a rare but known phenomenon. Sternal resection for this cancer is not completely investigated. For this reason, the aim of this study was to examine long-term survival and prognosticators for prolonged survival of our patients after sternal resection. Also, morbidity and mortality were investigated.Materials and Methods We retrospectively analyzed our prospective database of 20 patients who underwent a sternum resection (partial/complete) for BC in our institution between 2003 and 2014. Furthermore, patients with additional lung metastases were included. All patients received a mesh-methyl methacrylate technique (“sandwich technique”) and soft tissue coverage with myocutaneous muscle flap. Long-term outcomes and survival curves were performed by the Kaplan–Meier method. Survival differences and prognosticators were investigated using the log-rank test.Results Median survival was 32 months (95% confidence interval, 8–56 months). One-, 3-, and 5-year overall survivals were 79, 39, and 39%. There was a low morbidity and mortality with 35% (minor complications 30% and major complications 5%) and 0%. As prognosticators for longer survival, a positive hormone status (estrogen or progesterone) (p = 0.070) showed a trend. Neither age, primary mastectomy, disease-free interval < 24 months, primary N-status, nor preoperative chemotherapy showed a significant influence on survival. Furthermore, additional lung metastases did not influence survival significantly (p = 0.826).Conclusion Sternal resections for BC patients can be associated with promising long-term survival. R0 resection, good functional and cosmetic results are achievable with low morbidity and mortality. Patients with additional lung metastases should not be routinely excluded from resection and should be discussed in interdisciplinary tumor boards.
Keywords: breast cancer; sternal resection; loco-regional recurrence; sternum; reconstruction; lung metastases